Effect of [6]-gingerol on viral neuraminidase and hemagglutinin-specific T cell immunity in severe influenza - Avijit Dutta; Sung-Han Hsiao; Chen-Yiu Hung; Chia-Shiang Chang; Yung-Chang Lin; Chun-Yen Lin; Tse-Ching Chen; Ching-Tai Huang (Elsevier, 2023)
Background: H1N1 influenza viruses are the leading cause of severe respiratory virus infections worldwide. Resistance to the current selections of anti-influenza agents are still of concern. The Zingiber officinale root is one of the most heavily consumed dietary substances. It is also been traditionally used against common cold in Ayurveda and Chinese herbal medicine. Purpose: Investigation on in vitro and in vivo effect of [6]-gingerol from Zingiber officinale against influenza virus infection. Methods: In vitro antiviral property of [6]-gingerol was measured by the plaque reduction assay in which MDCK cells were infected with PR8 strain of H1N1 influenza A virus in the presence of gingerol. Gingerol-mediated inhibition of influenza neuraminidase activity was tested by MUNANA assay in vitro. In vivo activity was tested in PR8 strain of H1N1 influenza virus infected mice. Modulation of anti-influenza immunity was tested by the study of hemagglutinin-specific T cells in vivo. Results: [6]-Gingerol significantly reduced in vitro infection by PR8 strain of H1N1 influenza virus, with an IC50 value 2.25±0.18 μM. The inhibition was associated with the inhibition of viral neuraminidase activity, over 75% of the NA enzymatic activity of 2.5 × 103 PFUs of PR8 strain influenza virus at a concentration of 2 μM. Oseltamivir (Tamiflu) served as a positive control, which inhibited the NA enzymatic activity with an IC50 value of 1.88±0.05 μM. In H1N1 influenza virus infected mice, gingerol treatment (oral, once daily for 5 days) reduced virus load in the lungs and attenuated body weight loss and mortality. Gingerol inhibited viral neuraminidase-mediated intracellular TGF-β activation of lung-infiltrating CD4+ T cells. With the constrained active-TGF-β and immune suppression, influenza hemagglutinin-specific Th1 and Th17 immunity was increased. Conclusion: [6]-Gingerol from Z. officinale is a potent anti-influenza compound that inhibits viral neuraminidase activity and boosts hemagglutinin-specific CD4+ T cell response to the infection. Taken together, gingerol has the potential to be further evaluated for clinical applications in human influenza.